Footedness for scratching itchy eyes in rodents. Issue 1985 (26th October 2022) - Katayama, Yukitoshi; Miura, Ayane; Sakamoto, Tatsuya; Takanami, Keiko; Sakamoto, Hirotaka
Abstract : The neural bases of itchy eye transmission remain unclear compared with those involved in body itch. Here, we show in rodents that the gastrin-releasing peptide receptor (GRPR) of the trigeminal sensory system is involved in the transmission of itchy eyes. Interestingly, we further demonstrate a difference in scratching behaviour between the left and right hindfeet in rodents; histamine instillation into the conjunctival sac of both eyes revealed right-foot biased laterality in the scratching movements. Unilateral histamine instillation specifically induced neural activation in the ipsilateral sensory pathway, with no significant difference between the activations following left- and right-eye instillations. Thus, the behavioural laterality is presumably due to right-foot preference in rodents. Genetically modified rats with specific depletion of Grpr- expressing neurons in the trigeminal sensory nucleus caudalis of the medulla oblongata exhibited fewer and shorter histamine-induced scratching movements than controls and eliminated the footedness. These results taken together indicate that the Grpr -expressing neurons are required for the transmission of itch sensation from the eyes, but that foot preference is generated centrally. These findings could open up a new field of research on the mechanisms of the laterality in vertebrates and also offer new potential therapeutic approaches to refractory pruritic eye disorders.